Trigeminal Neuralgia Etiologi, Patofisiologi, dan Tatalaksana - Pricilla Y Gunawan; Annisa Dina (Medicinus, 2019)
Neuralgia trigeminal is unilateral, chronic and recurring facial pain syndromes, in which pain is distributed following trigeminal nerve branches and is commonly found in healthcare practice. The prevalence of trigeminal neuralgia is 4,3 / 100.000 case worldwide. As a facial pain syndrome, trigeminal neuralgia is well-known for reducing quality of life of its sufferers, hence the etiology, pathophysiology, and the management of trigeminal neuralgia are important to be recognized in daily clinical practice.